Speciation transformation of Pb during palygorskite sorption-calcination process: Implications for Pb sequestration. (January 2021) - Wang, Zhao; Jiang, Yunbin; Mo, Xinxin; Gu, Xueyuan; Li, Wei
Abstract: In this work, palygorskite was used to immobilize Pb using a sorption-calcination method. The speciation transformation of Pb during the process was characterized using surface complexation modeling (SCM), X-ray photoelectron spectroscopy (XPS), powder X-ray diffraction (XRD), 27 Al and 29 Si solid state nuclear magnetic resonance (NMR) spectroscopy and field emission scanning electron microscopy (FESEM). Results showed that Pb was adsorbed at permanently charged sites in the form of outer-sphere surface complexes at pH < 6 and [Pb(II)] < 0.5 mM, whereas inner-sphere ≡SOPbOH complexes formed under alkaline conditions. At high [Pb(II)] (e.g., 2 mM), Pb3 (CO3 )2 (OH)2 precipitate was observed. Since desorption experiments implied that sorbed Pb on palygorskite was labile, Pb-sorbed palygorskite was then heated at 200 and 800 °C, which suggested that thermal treatment effectively stabilized Pb(II), with no observable desorption after heating at 800 °C. Such stabilization is caused by the transformation of surface sorbed Pb(II) to Pb-containing enstatite based on XRD, SEM and solid state NMR characterizations. Overall, this study demonstrates a promising Pb stablization method in which Pb would be sorbed by palygorskite and sequestrated in the subsquent thermal treatment, leading to an effective immobilization of Pb. Graphical abstract: Image 1 Highlights: Palygorskite-based sorption-calcination method was used to immobilize Pb. Palygorskite can induce high concentration Pb to form hydrocerussite (Pb3 (CO3 )2 (OH)2 ) precipitate. Sorbed Pb by palygorskite transformed into the Pb-enstatite ceramic product during calcination at 800 °C. Leaching test showed Pb-enstatite phase exhibited excellent stability.